Sosialisasi Budaya Hibualamo Sebagai Support System untuk Mencegah Bunuh Diri Pada Pemuda di Desa Upa-Kali Upa - Seipattiseun, Mourits G. Y.; Side, Yafet; Katiandagho, Evelyne; Wolinelo, Elsa; Dungir, Gelsy M.; Patalatu, Jonherz Stenlly (Alamtana: Jurnal Pengabdian Masyarakat UNW Mataram, 2025)
Suicide is an act committed with the intention of ending one's own life. Suicide is caused by many factors, such as stress and depression. Data from the National Police Criminal Information Center shows that there have been 594 cases of suicide in Indonesia from January 1 to May 28, 2020. This figure shows that suicide is a serious problem that needs to be prevented so that the number does not continue to increase. Therefore, this community service project focuses on suicide prevention using the Hibua Lamo cultural approach. The goal of this project is to strengthen the social resilience of the community, especially the youth of Upa-Kali Upa, so that the community becomes a component that strengthens and protects each other. The methods used in this project consist of three stages, namely observation, preparation, implementation, and evaluation. The results obtained were an increase in the awareness of the youth of the village of Upa-Kali Upa regarding the importance of culture as an alternative that can be used to prevent suicide.